Pengaruh Sosial Media Marketing dan Advertising Terhadap Keputusan Berlangganan Spotify Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus - Londong, Jerliyen Pramita; Paridi, Andryanus; Patandean, Eben Hezer; Patanduk, Josua Krisna (Journal of Marketing Management and Innovative Business Review, 2023)
This research aims to see the influence of the use of Social Media Marketing and Advertising on Spotify subscription decisions among students at Paulus Indonesian Christian University. This research was carried out at the UKIP Makassar campus, where all students were the population of this research. Samples were taken using the Slovin formula and results were obtained from 100 people. The analysis was carried out using the SmartPLS version 4 application. The research results showed that both Social Media Marketing and Advertising had a positive and significant influence on UKIP Students' decision to subscribe to Spotify.